Effect of pasture as sole feed and herbage allowances on voluntary intake of dairy ewes - Hassoun P.; Autran P.; Aurel M.R.; Jamot J.; Baumont R.; Bocquier F. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Two experiments were conducted (E1) and (E2) with multiparous Lacaune dairy ewes in late lactating stage. The ewes were fed only pasture (cocksfoot E1, Italian ray grass E2) without supplementation except in E1 (+200 g dehydrated alfalfa/d/e). Pasture was available for about 6 hours, in daytime between the 2 milkings. During the time left, they were kept indoors with water and a salt block. In E1, 3 groups of 16 ewes divided on body weight (BW: 70 ± 6kg) body condition score (BCS: 3.2± 0.3) and milk yield (MY: 0.9 ± 0.2l/d) basis were offered one of the three different herbage allowances (namely L1, M1 and H1): low (1.4), medium (1.9) and high (2.4 kg DM/d/ewe) respectively. Each group was strip grazed for 3 weeks. In E2, 2 groups of 24 ewes were divided on the same criteria: (BW: 70±6kg), (BCS: 3.2±0.2) and (MY: 1.0± 0.3 l/d) were offered one of the 2 herbage allowances (namely L2 and M2): low (1.4) or medium (1.9 kg DM/d/ewe) respectively. In both experiments, 4 (E1) or 8 (E2) ewes per group were daily dosed with Ytterbium oxide as faecal marker. In E1, DM intake of ewes in L1, M1 and H1 was 1.3 ±0.3, 1.7±0.3 and 1.7±0.2 kg/d respectively. There were no differences (P>0.05) in BW (67.1±6.5 kg), BCS (3.0±0.2), milk yield (0.7±0.2 l/d), milk fat (MF 86±10 g/l) and milk protein (MP 60± 6 g/l) contents. In E2, due to a severe dry season, the experiment was shortened (less than 2 weeks). Herbage allowance was maintained by means of increasing paddock area. Nevertheless, daily DM intake of B2 and M2 groups was dramatically low: 0.49±0.12 and 0.68±0.12 kg respectively. There were no differences (P>0.05) in BW (64.6±5.3 kg), BCS (2.9±0.2), milk yield (0.9±0.2 l/d), MF (93±9 g/l) and MP (56±4 g/l) contents. In conclusion, dairy ewes intake did not exceed 1.7 kg DM/d at pasture when milk yield was low (end of lactation) and with only 6 hours grazing. When grass is offered at a low level, and when intake is very low, the ewes still maintain the milk yield (on a short time) but probably part of their energy requirements is mobilised from the body reserves. Experiments should be carried out at an earlier stage of lactation in order to reveal a more pronounced effect of herbage allowance at pasture.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)